Use of the Phen‐NaDPO:Sn(SCN)2 Blend as Electron Transport Layer Results to Consistent Efficiency Improvements in Organic and Hybrid Perovskite Solar Cells - Seitkhan, Akmaral; Neophytou, Marios; Kirkus, Mindaugas; Abou‐Hamad, Edy; Hedhili, Mohamed Nejib; Yengel, Emre; Firdaus, Yuliar; Faber, Hendrik; Lin, Yuanbao; Tsetseris, Leonidas; McCulloch, Iain; Anthopoulos, Thomas D. (Advanced functional materials, 2019)
A simple approach that enables a consistent enhancement of the electron extracting properties of the widely used small‐molecule Phen‐NaDPO and its application in organic solar cells (OSCs) is reported. It is shown that addition of minute amounts of the inorganic molecule Sn(SCN)2 into Phen‐NaDPO improves both the electron transport and its film‐forming properties. Use of Phen‐NaDPO:Sn(SCN)2 blend as the electron transport layer (ETL) in binary PM6:IT‐4F OSCs leads to a remarkable increase in the cells' power conversion efficiency (PCE) from 12.6% (Phen‐NaDPO) to 13.5% (Phen‐NaDPO:Sn(SCN)2). Combining the hybrid ETL with the best‐in‐class organic ternary PM6:Y6:PC70BM systems results to a similarly remarkable PCE increase from 14.2% (Phen‐NaDPO) to 15.6% (Phen‐NaDPO:Sn(SCN)2). The consistent PCE enhancement is attributed to reduced trap‐assisted carrier recombination at the bulk‐heterojunction/ETL interface due to the presence of new energy states formed upon chemical interaction of Phen‐NaDPO with Sn(SCN)2. The versatility of this hybrid ETL is further demonstrated with its application in perovskite solar cells for which an increase in the PCE from 16.6% to 18.2% is also demonstrated. The electron extracting properties of the widely used electron transporting layer (ETL) material Phen‐NaDPO are remarkably enhanced via simple addition of the wide‐bandgap inorganic material tin (II) thiocyanate (Sn(SCN)2). Use of this hybrid ETL system in organic and perovskite solar cells results in consistent efficiency improvements due to the reduced trap‐assisted recombination and efficient electron extraction.